Founding of blanks for lining of automobile engines cylinder blocks - V. F. Bevza; B. I. Bogdanov; V. A. Krasny; V. S. Mazko (Литьë и металлургия)
The article sets forth peculiarities of casting of blanks of cylinder liners of gray cast iron by freezing on without use of a kernel. It alleges mechanical properties and structure of the blanks.